Nafkah Keluarga Perspektif Istri Buruh Tani di Ponorogo - Zulfatur Rosidah; Agus Purnomo; Rohmah Maulidia (Institut Agama Islam Negeri Ponorogo, 2024)
This field research uses qualitative methods to analyze wives' perspectives regarding the income provided to the family, whether additional or main and to analyze the construction of farm workers' wives regarding income. Data collection was through interviews and observations. The collected data is then processed and analyzed using descriptive analytical techniques using an inductive mindset and drawing conclusions or verification. The research findings obtained regarding the perspectives of farm workers' wives regarding the income provided to the family are classified into two classifications. The wives of agricultural laborers who work believe that their wife's income is additional income. The two working wives believe the wife's income is not additional. The social construction of farmworker wives regarding livelihood cannot be separated from the three moments of the social construction of externalization, objectivation, and internalization. From these stages, the conclusion can be drawn: farmworker wives' livelihood is divided into two groups. The first group believes that the husband still bears maintenance. Second, she believes that maintenance in the family is not only borne by the husband but the wife is obliged to help support the family.